2013
DOI: 10.1164/rccm.201205-0839oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduced MicroRNA-150 Is Associated with Poor Survival in Pulmonary Arterial Hypertension

Abstract: Reduced circulating miR-150 levels are associated with poor survival in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 38 publications
2
119
1
1
Order By: Relevance
“…A growing body of literature supports the concept that irregularities in microRNA activity and related networks promote PAH pathophysiology, which creates exciting opportunities for precision therapeutics design (19,(41)(42)(43)(44). Rhodes and colleagues analyzed pulmonary artery endothelial cells from control subjects and subjects with IPAH, using RNA sequencing to determine novel pathways perturbed in relation to reduced BMPR2 signaling (45).…”
Section: Pah and The Concept Of Precision Medicinementioning
confidence: 99%
“…A growing body of literature supports the concept that irregularities in microRNA activity and related networks promote PAH pathophysiology, which creates exciting opportunities for precision therapeutics design (19,(41)(42)(43)(44). Rhodes and colleagues analyzed pulmonary artery endothelial cells from control subjects and subjects with IPAH, using RNA sequencing to determine novel pathways perturbed in relation to reduced BMPR2 signaling (45).…”
Section: Pah and The Concept Of Precision Medicinementioning
confidence: 99%
“…Several of these miR provide mechanistic insight [14] and prognostic utility [15] but discordance between models and clinical samples have reported [16].…”
Section: Editorialmentioning
confidence: 99%
“…Rhodes et al also showed, more specifically, that downregulation of microRNA-150 is associated with a reduced 2-year survival in patients with established PAH. 49 There currently is no data available in the specific population of patients with PAH-CHD and if the micro-RNA profile differs between reversible and irreversible PAH, although microRNAs are potentially a very interesting area of research in terms of circulating biomarkers.…”
Section: Myers Po Et Almentioning
confidence: 99%